2014
DOI: 10.3945/ajcn.113.075937
|View full text |Cite
|
Sign up to set email alerts
|

General and abdominal fat outcomes in school-age children associated with infant breastfeeding patterns

Abstract: Associations of infant breastfeeding and age at the introduction of solid foods with general and abdominal fat outcomes are explained by sociodemographic and lifestyle-related factors. Whether infant dietary composition affects specific fat outcomes at older ages should be further studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 49 publications
1
64
0
Order By: Relevance
“…No evidence of a specific critical period of development of overweight was observed. In a small longitudinal study by Péneau et al [3], it was suggested that the beneficial effects of breast-feeding on later body fatness could be counteracted by an imbalanced diet after the breast-feeding period, a finding corroborated by recent findings of the Generation R Study [4]. These findings indicate that deviations in the developmental pathways leading to childhood obesity are not limited to any specific period in childhood, which in fact supports a focus on appropriate nutrition and behavioral intervention strategies throughout childhood [5,6].…”
Section: Introductionsupporting
confidence: 67%
“…No evidence of a specific critical period of development of overweight was observed. In a small longitudinal study by Péneau et al [3], it was suggested that the beneficial effects of breast-feeding on later body fatness could be counteracted by an imbalanced diet after the breast-feeding period, a finding corroborated by recent findings of the Generation R Study [4]. These findings indicate that deviations in the developmental pathways leading to childhood obesity are not limited to any specific period in childhood, which in fact supports a focus on appropriate nutrition and behavioral intervention strategies throughout childhood [5,6].…”
Section: Introductionsupporting
confidence: 67%
“…exclusive breast fed, ever breast fed, never breastfed or duration of breastfeeding as well as the potential confounding variables controlled for. For example, in one study the strength of the association between breastfeeding and childhood obesity was reduced when factors such as maternal BMI, SES and smoking as well as child characteristics such as television watching are taken into account (Durmus et al, 2014)). Overall the data suggest that breastfeeding for more than 3-4 months decreases risk for childhood obesity but the effect is small (Beyerlein and von Kries, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…1 Thus, with the increase of children obesity prevalence, the interest in investigate if breastfeeding (BF) and the handle of complementary feeding introduction are associated with the risk of overweight and obesity in later stages of life. 2,3 The exclusive breastfeeding (EBF) has been associated to a minor risk of obesity in some studies. 2 Systematic revision which compiled the findings of over 80 surveys suggests that breastfeeding is associated to the reduction of 10-20% on the child obesity prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…3 Because of this, identifying feeding behaviors in childhood that predispose to obesity development is an important task in order to determine what factors can be modified, as well as the planning of interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation